Effect of multiple firings on the color and translucency of monolithic zirconia - Jiang, Lei; Xu, Meng-Qi; Lu, Xin-Ling; Tong, Xin-Wen; Liang, Xin-Jie; Yu, Hao (Frontiers in Materials, 2023)
The effects of multiple firings on the color and translucency of monolithic zirconia were investigated in this paper. One hundred specimens were milled using 3 types of monolithic zirconia: multilayered zirconia (UTML, Katana) (UT), highly translucent zirconia (Organic Translucent, R+K) (OT), and nanosized zirconia (DIAZIR ST9810, Zhong Xin Tang Guo Ye) (ST). The group UT was divided into 3 subgroups: the incisal (UT-I), middle (UT-M), and cervical (UT-C). After sintering (T0), the specimens of each group (n=20) were repeatedly fired 3 times. The L*, a*, and b* values were measured by using a spectrophotometer at T0, and after the first (T1), second (T2), and third (T3) firings. The translucency parameter (TP), contrast ratio (CR), opalescence parameter (OP), and color difference (∆E00) were calculated and statistically analyzed (α=0.05). The surface morphologies of the specimens were observed using SEM. Multiple firings significantly affected the OP and the ∆E00 values of the materials tested (both p<0.001). The ∆E00 values of group ST at T1-T3 were greater than the 50%:50% acceptability threshold (∆E00>1.8). Moreover, multiple firings did not exhibit significant effects on the TP and CR values of any materials (both p>0.05).The surface topographies of the specimens after multiple firings were quite similar. Changes in opalescence were found for the multilayered zirconia and nanosized zirconia after multiple firings, but the clinical significance was low. Clinically unacceptable color changes were found in the nanosized zirconia after multiple firings, which were attributed to the higher L* values and the lower b* values after multiple firings. However, the optical properties and composition of surface elements of multilayered 5Y-TZP with over 3 layers need to be investigated in future studies.